Progettazione di attività didattiche STEAM in ambito museale durante i due anni di pandemia Covid-19 - Domenici, Valentina (Chimica nella Scuola, 2022)
This work reports a discussion about the effect of pandemic Covid-19 on a methodology adopted in a course of ‘Chemical Education’ at the University of Pisa. This course aims to train future chemistry teachers and, since 2013-2014, a new methodology was implemented called ‘STEAM project-based learning’ which is centered on the development of educational activities in the non-formal context, in particular science museums and Open Days. The full description of the methodology is reported in ‘STEAM Project-Based Learning Activities at the Science Museum as an Effective Training for Future Chemistry Teachers’ (V. Domenici, Edu. Sci. 2022, 12, n. 30; see pag. 49 of this issue).